New model averaging on household income to examine poverty in Malaysia - Mohd Padzil, Siti Aisyah; Pillay, Khuneswari Gopal; Mohd Salleh, Rohayu; Azme, Sya Sya Avtar (2019)
Household income for Malaysian vary due to many factors as Malaysian’s are multiracial and multi religious. Malaysia is divided into two regions which are east and west Malaysia. Due to different geographical area, there’s a contrast on the development between these two regions. Even though the rate of poverty in Malaysia had been reduced yearly, the poverty rate of Malaysian still has not been eradicated. This research aims to examine the consequences of households differences (age, gender, marital status, education, activity and family size), states, region and net income to the cause of poverty among Malaysian. Model Averaging (MA) and New Model Averaging (NMA) will be compared based on